A novel oxygen carrier for chemical looping reforming: LaNiO3 perovskite supported on montmorillonite. (15th July 2017) - Li, Lin; Song, Yongchen; Jiang, Bo; Wang, Kaiqiang; Zhang, Qian
Abstract: In this study, a novel LaNiO3 perovskite-based oxygen carrier with montmorillonite (MMT) support is proposed for hydrogen production from chemical looping reforming. The MMT support with lamellar structure possesses high specific surface area and favorable dispersion effect, which can effectively suppress the agglomeration of LaNiO3 . Moreover, numerous spacing of MMT can facilitate the mass transfer of reactants and products, reducing the carbon deposition. The proposed LaNiO3 /MMT was synthesized by the sol-gel method and characterized by XRD, SEM, TEM and N2 adsorption-desorption measurements. Results revealed that the LaNiO3 nanoparticles were uniformly deposited onto the surface of MMT and the formed oxygen carrier exhibited large specific surface area. The activity and stability of LaNiO3 /MMT oxygen carrier were evaluated in a fixed-bed reactor. Results showed this new design with MMT support enhanced the activity of oxygen carrier, leading to a much higher ethanol conversion and H2 selectivity than that of conventional LaNiO3 . In addition, the long-term testing revealed the LaNiO3 /MMT oxygen carrier was more resistant to the deactivation than the LaNiO3 . In short, the novel LaNiO3 /MMT oxygen carrier developed in this work exhibits high redox activity and stability and provides a promising potential for chemical looping reforming in industrial application. Highlights: A novel LaNiO3 perovskite-based oxygen carrier with MMT support was developed. The MMT support enlarged the specific surface area of oxygen carriers. The developed LaNiO3 /MMT oxygen carrier yielded high redox activity and high stability. The LaNiO3 /MMT oxygen carrier exhibited a 19% improvement over the LaNiO3 in terms of H2 selectivity.